Paul Hoffmann and the cutaneous silent period test - Otto Jesus Hernández Fustes; Cláudia Suemi Kamoi Kay; Paulo José Lorenzoni; Renata Dal-Prá Ducci; Paula Raquel do Vale Pascoal Rodrigues; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria)
We herein present aspects of the biography of Professor Paul Hoffmann, covering his main works, mainly the article describing the cutaneous silent period, a new technique when it was published in 1922, with a review of its importance, its role in clinical neurophysiology, and its clinical application.